Experimental Study on Bond-Slip Behavior between Corroded I-Shaped Steel and Concrete in Subsea Tunnel - Wang, Mingnian (Materials (Basel), 2019)
Degradation of the bond between I-shaped steel and concrete due to the corrosion of I-shaped steel significantly affects the durability of steel reinforced concrete (SRC) structures. This study carried out the accelerated corrosion test and push-out test to study the bond-slip behavior and characteristics considering the corrosion of I-shaped steel, and test results indicated that: (1) The performance degradation of the bond-slip accelerated when the corrosion ratio reached 12%. (2) The corrosion failure pattern of SRC experienced slip phase and destruction phase in the rising stage. (3) Based on the principle of minimum potential energy, the bond stress was obtained only with the load and the displacement in the free end and the loading end. (4) Meanwhile, a new bond-slip degradation model was developed using the interface damage theory. Finally, the proposed model agreed with the experimental results.